Compactação em solos coesos dos tabuleiros costeiros de Alagoas - OLIVEIRA, Veronildo Souza de (2008)
The sugarcane cultivation requires an intensive use of agricultural machinery for tillage and crop procedures; however, compression effect on soil caused by passage of agricultural machinery has been little studied in the last years. Deformations due to continuous traffic of agricultural machinery and implements in association with inadequate managements have been observed to decrease the sustainability of agricultural soils, mainly because of alterations of some soil physical attributes which can make the soil more susceptible to compaction. The objective of this work was to evaluate the susceptibility to compaction of a Yellow Argissol submitted to three distinct managements of sugarcane cultivation and native forest, through aggregate stability and distribution, compaction and compressibility characteristics of the soil. Four distinct areas were investigated: a native forest (NF), an area cultivated with sugarcane without irrigation (ANI), an irrigated area (AWI), and an area irrigated with vinasse (AIV). Soil samples were collected randomly, in 50.00×50.00m-area, at depths ranging from 0 to 20 cm, 20 to 40 cm, and 40 to 60 cm. For assessment of aggregate stability and distribution it was evaluated total organic carbon (TOC) content, wet aggregate stability, aggregate stability index (ASI), module of thinness (MT), and percentage of aggregates larger than 2.0 mm stable in water (AGRI). For compaction analyses, undeformed soil samples were collected with metallic rings and were used for the determination of soil density. Deformed samples were used for the determination of organic matter content and the performance of Standard Proctor tests. Regarding the compressibility analyses, a trench was dug in the four selected areas and four underformed samples were collected in each depth. The samples were collected using metallic rings with 6.4 cm in diameter and 2.5 cm in height, at 0-20, 20-40 cm, with four replicates. In laboratory, the samples were previously saturated and submitted to soil suctions raging from 0.1 to 1500. Confined compression tests were performed with the saturated samples. Data were submitted to variance analysis and the differences among means were compared using the Tukey test at 5% of probability. In all areas, the results pointed out decrease in aggregate stability as the soil depth increased for classes higherthan 2.0 mm. The aggregation indexes of the cultivated areas were comparatively smaller than that of the native forest following the sequence NF>AIV>AWI >AWI. The management AWI showed the smallest aggregation indexes and AIV was the most close to NF. Significant and positive correlations occurred between The management that more closely approached the native forest conditions was the vinasse management (MWV), which showed better aggregate stability under water. Significant and positive correlations were obtained between TOC and stability indexes studied. Data of maximum capacity of soil compaction followed the crescent order of compaction susceptibility ANI>AWI>AIV>NF, and the critical humidity the inverse order. A regression analysis for pre-consolidation stress in function of water content (Ug) and correlations among the several variables were carried out. In all investigated areas, the depth of 0 to 20 cm showed to be more susceptible to compaction than 20 to 40 cm; the AIV management modified the compressive behavior of the soil in both depth ranges (0-20 and 20-40 cm); and the load support capacity of the soil was larger in the depth of 20 to 40 cm.